Ritual Dynamics and Spiritual Practices in the Teaching of Tarekat Qadiriyah wa Naqsyabandiyah - Priyana, Yana; Rusdi, Muhammad; Muhammadong, Muhammadong; Tjahyadi, Indra; Imron, Ali (Westscience Press, 2024)
This study explores the intricate dynamics of rituals and spiritual practices within the Tarekat Qadiriyah wa Naqsyabandiyah, a prominent Sufi order in Indonesia. Through a comprehensive literature analysis, in-depth interviews, and participant observation, the research delves into the historical evolution, theological foundations, and the multifaceted role of rituals and spiritual exercises in shaping the followers' spiritual journey. The findings reveal that the integration of Qadiriyah and Naqsyabandiyah traditions fosters a unique spiritual path that balances exoteric religious observance with esoteric contemplation. Key themes include the transformative impact of rituals, the pivotal role of the sheikh, the significance of communal practices, and the holistic pedagogical approaches employed within the Tarekat. The study concludes that these rituals and practices are central to individual and collective spirituality, providing a cohesive and supportive spiritual community. This research contributes to the broader understanding of Indonesian Sufism and the enduring relevance of Sufi practices in contemporary Islamic spirituality.